Chemometric Analysis Based on GC-MS Chemical Profiles of Three Stachys Species from Uzbekistan and Their Biological Activity - Haidy A. Gad; Elbek A. Mukhammadiev; Gokhan Zengen; Nawal M. Al Musayeib; Hidayat Hussain; Ismail Bin Ware; Mohamed L. Ashour; Nilufar Z. Mamadalieva (Plants, 2022)
The chemical composition of the essential oils (EOs) of Stachys byzantina, S. hissarica and S. betoniciflora growing in Uzbekistan were determined, and their antioxidant and enzyme inhibitory activity were assessed. A gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of 143 metabolites accounting for 70.34, 76.78 and 88.63% of the total identified components of S. byzantina, S. hissarica and S. betoniciflora, respectively. Octadecanal (9.37%) was the most predominant in S. betoniciflora. However, n-butyl octadecenoate (4.92%) was the major volatile in S. byzantina. Benzaldehyde (5.01%) was present at a higher percentage in S. hissarica. A chemometric analysis revealed the ability of volatile profiling to discriminate between the studied Stachys species. The principal component analysis plot displayed a clear diversity of Stachys species where the octadecanal and benzaldehyde were the main discriminating markers. The antioxidant activity was evaluated in vitro using 2,2-diphenyl-1-picryl-hydrazyl (DPPH), 2,2-azino bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), cupric reducing antioxidant capacity (CUPRAC), ferric reducing power (FRAP), chelating and phosphomolybdenum (PBD). Moreover, the ability of the essential oils to inhibit both acetyl/butyrylcholinesterases (AChE and BChE), α-amylase, α-glucosidase and tyrosinase was assessed. The volatiles from S. hissarica exhibited the highest activity in both the ABTS (226.48 ± 1.75 mg Trolox equivalent (TE)/g oil) and FRAP (109.55 ± 3.24 mg TE/g oil) assays. However, S. betoniciflora displayed the strongest activity in the other assays (174.94 ± 0.20 mg TE/g oil for CUPRAC, 60.11 ± 0.36 mg EDTA equivalent (EDTAE)/g oil for chelating and 28.24 ± 1.00 (mmol TE/g oil) for PBD. Regarding the enzyme inhibitory activity, S. byzantina demonstrated the strongest AChE (5.64 ± 0.04 mg galantamine equivalent (GALAE)/g oil) and tyrosinase inhibitory (101.07 ± 0.60 mg kojic acid equivalent (KAE)/g) activity. The highest activity for BChE (11.18 ± 0.19 mg GALAE/g oil), amylase inhibition (0.76 ± 0.02 mmol acarbose equivalent (ACAE)/g oil) and glucosidase inhibition (24.11 ± 0.06 mmol ACAE/g oil) was observed in S. betoniciflora. These results showed that EOs of Stachys species could be used as antioxidant, hypoglycemic and skincare agents.